An analysis of relationships between educational practices framed by the NSDC staff development standards, socioeconomic status, and third grade reading achievement - Fertitta, Dawn M., author; Lehmann, Jean P., advisor; Gloeckner, Gene W., committee member; Timpson, William, committee member; McCambridge, James, committee member (Colorado State University. Libraries, 2005)
This random sample, retrospective comparative research was conducted to examine relationships between the National Staff Development Council (NSDC) staff development standards (SDS) individually; constructs of context, process, and content; collective use (CU); hours of professional development each month (HPD/M); and percent of free and reduced lunch (%FRL) in relation to third grade reading achievement (3RA) of proficient and advanced (P&A) in Colorado. Participants were 69 elementary teachers with 5+ years or greatest experience; 25.27% response rate. The NSDC Standards Assessment Inventory, two additional questions, and 2004 third grade reading Colorado Student Assessment Program were used to answer: (1) What are professional development practices (PDP), %FRL, and 3RA of elementary schools in Colorado? (2) Do PDP or %FRL differ in high and low achieving schools? (3) Are links evident between PDP, %FRL, and P&A? (4) Can PDP or %FRL predict P&A individually or in combination? Data sets (DS) included returned sample (RS), highest achieving 10% (H10%), highest achieving 25% (H25%), lowest achieving 25% (L25%), and lowest achieving 10% (L10%). The RS and accessible population of Colorado were statistically similar. There were no statistical differences in PDP between high and low achieving schools. Descriptive statistics showed SDS practiced in the frequently-to-always range was four-H10%, five-H25%, two-L25%, seven-L10%, and two-RS. The H10%, H25%, and L25% DS practiced content construct to highest degree. The L10% practiced process construct to highest degree. Leadership and equity standards ranked first or second and learning communities and evaluation standards ranked equally low across all DS. Family involvement standard ranked 12th L10%, 10th L25% and RS, 8th H25%, and 4th H10%. HPD/M was 13.2-RS, 12.23-L25%, 10.41-L10%, 10.31-H25%, and 8.71-H10%. Open-ended question reflected additional PDP related to achievement. Differences between H10% and L10% showed %FRL was significant, p < .01. Differences between H25% and L25% indicated %FRL was significant, p < .001. Null hypotheses were rejected for %FRL. Null hypotheses accepted for all SDS, constructs, CU, and HPD/M. RS held one significant correlation between %FRL and P&A, p < .01. Larger than typical negative relationship r (- .682) showed greater %FRL at a school the lower the P&A statistic. Second, L25% held one significant correlation between %FRL and P&A, p < .01, larger than typical negative relationship of r (- .616). Null hypotheses for associations between %FRL and P&A for RS and L25% were rejected. Linear regression indicated %FRL significantly, p < .001 predicted P&A; prediction equation = 90.171 + - .415(%FRL of school). Adjusted R2 = .491 showed 49% of variance in P&A was explained by %FRL. CU did not predict P&A. Null hypothesis was rejected for %FRL. Statistics suggested schools of all achievement levels exhibited similar PDP. A call for future research and policy modification to promote equal opportunities for all students and educators was presented. Suggestions for future research included factors of poverty contributing to reduced achievement; funding programs known to create environments conducive to high achievement; equitable funding formulas; high-stakes testing and achievement; achievement related to federal sanctions and organizational development; family involvement; circumstances of professional development programming and emphasis; survey development identifying practices limiting achievement; and expansion of research in Colorado and other states. Federal, state, district, and building policy implications included modifying funding formulas; eliminating discrepancies of identified student groups; continuing professional development initiatives; promoting low-stakes testing; eliminating sanctions associated with low achievement; accountability measures based on standards of practice; affirming a common professional development definition, program plan to implement standards of practice, and eliminating barriers; funding supportive collaboration; increasing family and community support; and increasing program options through adequate school district funding. Federal and state legislators working with educators, families, and communities can accomplish the attainable goal of increased achievement for all students.
Keywords: school administration; teacher education; literacy; educational administration